Reliability of coding causes of death with ICD-10 in Germany - Winkler, Volker; Ott, Jördis Jennifer; Becher, Heiko (International journal of public health, 2010)
The international classification of diseases (ICD) is used to code death worldwide uniformly and comparably. This study investigates the reliability of national ICD-10 coding practice by assessing agreement of two official coding offices in Germany.
Published: 28 July 2009
Gesehen am 26.02.2024